1995
DOI: 10.1039/c39950002483
|View full text |Cite
|
Sign up to set email alerts
|

Novel insertion of dimethylsilanone into an Yb–N bond and molecular structure of the insertion product [{Yb(η2-C3N2HMe2-3,5)(µ-η12-OSiMe2C3N2HMe2-3,5)(η-C5H4Me)}2]

Abstract: When 5)2(C5H4Me)l (C3N2H2Me2-3,5 = 3,5-dimethylpyrazole) is recrystallized by slow diffusion of hexane into a thf solution which contains a small amount of dimethylsilicone grease, it is converted into to the unexpected complex [{Yb(rl2-C3N2HMe2-3,5)(~-rll:y2-OSiMe2C3N2HMe2-3,5)(r-CgHqMe)}2l indicating a novel Me2Si0 insertion react ion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 18 publications
1
8
1
Order By: Relevance
“…Figure B) originates from trace silicone [(H 3 C) 2 SiO] n concentrations in the THF reaction mixture with the surplus oxygen removed at the sodium metal mirror surface. This is consistent with the previous literature assumptions.
2 Total-reflection X-ray fluorescence spectra of the reaction solution containing 9,9-dimethylsilafluorene (- - -), of THF dried over Na (···), and of THF dried over molecular sieves () (the circle insert shows Si peaks).
…”
supporting
confidence: 91%
See 1 more Smart Citation
“…Figure B) originates from trace silicone [(H 3 C) 2 SiO] n concentrations in the THF reaction mixture with the surplus oxygen removed at the sodium metal mirror surface. This is consistent with the previous literature assumptions.
2 Total-reflection X-ray fluorescence spectra of the reaction solution containing 9,9-dimethylsilafluorene (- - -), of THF dried over Na (···), and of THF dried over molecular sieves () (the circle insert shows Si peaks).
…”
supporting
confidence: 91%
“…An extensive literature search reveals that the inclusion of one , and up to seven (H 3 C) 2 SiO subunits into organometallic compounds under reductive conditions has been repeatedly reported, yielding, for example, an ytterbium pyrazole compound, the hexameric lithium dimethylnaphthylsilanolate, or an indium complex containing a K[OSi(CH 3 ) 2 ] 7 solvated cation the silicon content has been assumed to result from the easily ether-soluble dimethylsiloxane grease used to seal the glass fittings. …”
mentioning
confidence: 99%
“…For example, the latter feature is responsible for isonitrile insertion into Ln−N bonds and it explains the key steps in the catalytic hydroamination/cyclization of aminoolefins . Very recently, the proximity of silicon- and nitrogen-containing moieties even allowed the unprecedented insertion reaction of a dimethylsilicone into a Ln−N(amide) bond . Readily available and routinely employed compounds Ln[N(SiMe 3 ) 2 ] 3 were chosen to evaluate the reaction of 1 .…”
Section: Resultsmentioning
confidence: 99%
“…However, the preparations of 4 and 8 demonstrate the utility of this methodology. Interestingly, a previous study reported that only two cyclopentadienyl ligands were replaced upon treatment of tris(cyclopentadienyl)lanthanide(III) complexes with pyrazoles. ,
…”
Section: Resultsmentioning
confidence: 99%